Penguatan Profil Pelajar Pancasila Siswa Kelas VII SMP Negeri 15 Mataram melalui Implementasi Model Pembelajaran Berbasis Karakter pada Pembelajaran Bahasa Indonesia - Hasan; Rahmat Hidayat; Lutfi Qurratul Aini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to strengthen the Pancasila Student Profile of seventh-grade students at SMP Negeri 15 Mataram through the implementation of a character-based learning model in Indonesian language instruction. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action implementation, observation, and reflection stages. The research subjects were 27 students of class VII D. Data were collected through observation, attitude assessment, and documentation. The observed indicators of the Pancasila Student Profile included cooperation, independence, critical reasoning, and integrity. The results showed an improvement in the achievement of the Pancasila Student Profile among students. In Cycle I, the achievement percentage reached 62% and was categorized as fair, while in Cycle II it increased to 85% with a very good category. In addition, students’ activeness, discipline, and responsibility in Indonesian language learning also showed significant improvement. Therefore, it can be concluded that the implementation of a character-based learning model is effective in strengthening the Pancasila Student Profile of seventh-grade students at SMP Negeri 15 Mataram.